Smoke exposure as a risk factor for developing pneumonia in children under five years old in Choloma, Honduras. A case control study in a public health center from July to October 2016. - Figueroa Avilez, Paola Estela; Vallecillo, Hilda Janin; Chávez, Sandra (Open Science Journal, 2022)
Background: Pneumonia is the main cause of death during childhood in developing countries. The risk factors for developing pneumonia include age, preterm birth, low birth weight, malnutrition, poverty, comorbidities and environmental factors like smoke exposure. Air pollution increases the risk of respiratory tract infections, hospitalizations, severity of pneumonia and death during childhood. This study was designed to identify if the smoke exposure and type of smoke is a significant risk factor for developing pneumonia in children under five years in Choloma, Honduras. Methods: Honduras during four months since July 2016 to October 2016. The study included a total of 52 children under five years (26 cases and 26 controls) to determine if they were exposed to smoke at home and if that condition was related to development of pneumonia. Cases were selected at the time of diagnosis. The controls were selected matching the age of the cases. Data was collected through an interview. Written informed consent was requested. Results: Pneumonia was more frequent among children under two years, males, children with incomplete vaccination according to age, children with comorbidities like asthma and children from families who live in extreme poverty. Smoke exposure was more frequent among children diagnosed with pneumonia (93.3% vs 19.2%). The most common source of smoke was wood used as fuel for cooking. Smoke exposure was a significant risk factor for developing pneumonia, wood smoke, tobacco smoke and industrial smoke showed higher risk for developing pneumonia. Smoke from burning trash was more frequent among children diagnosed with pneumonia but this condition was not statistically significant. Conclusion: smoke exposure is a risk factor for developing pneumonia in this population. Wood smoke and tobacco smoke are the main sources of exposure in this population.